2014
DOI: 10.1186/2049-9957-3-1
|View full text |Cite
|
Sign up to set email alerts
|

Control of malaria and other vector-borne protozoan diseases in the tropics: enduring challenges despite considerable progress and achievements

Abstract: Vector-borne protozoan diseases represent a serious public health challenge, especially in the tropics where poverty together with vector-favorable climates are the aggravating factors. Each of the various strategies currently employed to face these scourges is seriously inadequate. Despite enormous efforts, vaccines—which represent the ideal weapon against these parasitic diseases—are yet to be sufficiently developed and implemented. Chemotherapy and vector control are therefore the sole effective attempts to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 66 publications
4
81
1
1
Order By: Relevance
“…Similar results were reported in studies conducted in rural communities of Abeokuta of Nigeria [36], in Senegal [41], and in Loum, Cameroun [42]. In contrast to our findings, a study carried out in Zimbabwe found satisfactory efficacy with praziquantel after the first dose [43].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar results were reported in studies conducted in rural communities of Abeokuta of Nigeria [36], in Senegal [41], and in Loum, Cameroun [42]. In contrast to our findings, a study carried out in Zimbabwe found satisfactory efficacy with praziquantel after the first dose [43].…”
Section: Discussionsupporting
confidence: 90%
“…We found high treatment failures amongst 13 and 14 years old children with heavy intensity. CR and failure cases observed were consistent with findings in a study conducted in Abeokuta, Nigeria [36]. A high load of eggs in the urine indicates implicitly a high number of mature worms, which may require a higher dose than the standard dose.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Malaria continues to be a major global public health problem with about half of the global population (3.2 billion people) at risk in more than 106 endemic countries [3]. With an estimated 0.65-1.2 million deaths annually, it accounts for about 40 to 45 million DALYs (Disability-Adjusted Life Years) [4] and the cost to Africa alone in lost Gross Domestic Product (GDP) is estimated at £7.13 billion annually which accounts for 40% of the continent's public health spending [5].…”
Section: Introductionmentioning
confidence: 99%
“…In Cameroon, malaria accounts for 30% of all morbidity cases, 36% of outpatient consultations, 67% of childhood deaths and 48% of all hospital admissions [8,9].…”
Section: Introductionmentioning
confidence: 99%